Abrangência dos relatórios de responsabilidade social e corporativa divulgados por empresas brasileiras - Costa, Benedito Manoel do Nascimento (2016)
The objective of this study is to evaluate the level of comprehensiveness of corporate social responsibility (CSR) of Brazilian companies. The literature suggests that comprehensive disclosure must be contextualized, incorporating concrete information actions and social performance, and not only the intentions. Thus, a comprehensive report, as such, requires three types of information for each item of CSR disclosed: vision and objectives, management actions and performance indicators. To assess the level of coverage of RSC reports, we proceeded to a content analysis of 265 CSR reports of 98 Brazilian companies listed on the BM&FBovespa that followed the guidelines of the Global Reporting Initiative (GRI) in the period 2010-2013. The results indicate that, although still low completeness of the contents of CSR reports, there has been an increasing degree of comprehensiveness over the study period. In addition, there are factors that affect the level of coverage of CSR reports. Companies that have sought greater exposure of their concerns and social aspects of sustainability, such as the companies of the Corporate Sustainability Index (ISE), have higher coverage levels. It is also worth mentioning that companies in sectors considered to have higher environmental impact have the highest level of environmental coverage, as well as the existence of one major shareholder positively influences the level of completeness of CSR reports of Brazilian firm.